2017
DOI: 10.3389/fnbeh.2017.00147
|View full text |Cite
|
Sign up to set email alerts
|

Motor Timing and Covariation with Time Perception: Investigating the Role of Handedness

Abstract: Time is a fundamental dimension of our behavior and enables us to guide our actions and to experience time such as predicting collisions or listening to music. In this study, we investigate the regulation and covariation of motor timing and time perception functions in left- and right-handers who are characterized by distinct brain processing mechanisms for cognitive-motor control. To this purpose, we use a combination of tasks that assess the timed responses during movements and the perception of time interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 72 publications
0
4
0
6
Order By: Relevance
“…It is also important to distinguish between motor and perceptual timing. The first refers to the execution of a motor act to represent a temporal interval, as in the case of a time-line bisection task (e.g., Vicario, 2011 ), temporal production/reproduction ( Vicario et al, 2011a , b ), finger tapping ( O’Regan et al, 2017 ), and movement synchronization ( Vicario, 2012 ). The second involves a time comparison task, such as performing a task of discrimination between the duration of a reference and the duration of a target stimulus (e.g., Grondin et al, 1999 ; Vicario et al, 2009 , 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to distinguish between motor and perceptual timing. The first refers to the execution of a motor act to represent a temporal interval, as in the case of a time-line bisection task (e.g., Vicario, 2011 ), temporal production/reproduction ( Vicario et al, 2011a , b ), finger tapping ( O’Regan et al, 2017 ), and movement synchronization ( Vicario, 2012 ). The second involves a time comparison task, such as performing a task of discrimination between the duration of a reference and the duration of a target stimulus (e.g., Grondin et al, 1999 ; Vicario et al, 2009 , 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the subsequent years, studies have repeatedly shown that motor activity and time perception are not only correlated, but interdependent. Thus, for example, O’Regan et al ( 2017 ) observed an interrelationship between handedness, timed motor behaviour, and time experience. Interval timing is also a critical part of the experience of music, and while music perception is well known to affect time perception, it is now becoming clear that musical action and embodiment affect how we experience music in time (Maes et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that handedness not only affects the sensorimotor control mechanisms (Klöppel, et al 2007 ; Pool, et al 2014 ; Reid & Serrien, 2014 ; Serrien, et al 2012 ) but also influences how individuals attend to and respond to the environment. In other words, handedness influences a range of abilities that involves visuospatial functions (Bareham, et al 2015; Hécaen & Sauguet, 1971 ; O’Regan & Serrien, 2018 ; Vogel, et al 2003 ), attentional regulation in space and time (Buckingham et al, 2009 ; O’Regan, et al 2017 ) and visual processing in perihand space (Le Bigot & Grosjean, 2012 ). Combined, these findings illustrate that handedness has a widespread impact on the processing requirements of space and time for meeting behavioural goals.…”
Section: Introductionmentioning
confidence: 99%